Gamification System to Improve Student Learning Motivation: A Case Study in President University - Juwono, Ronny; Almi, Raihan (President University, 2024)
Abstract— Student engagement is a crucial factor influencing learning outcomes in both traditional and modern education systems. Traditional approaches often struggle to sustain high levels of motivation and participation, particularly when students have diverse interests and learning preferences. This study explores the integration of a gamification system into the learning process to enhance student engagement at President University. The proposed system comprises three core components: (1) a Gamification App (Android & iOS) designed for students, incorporating game mechanics such as points, leaderboards, and rewards; (2) a Gamification Web Portal, which serves as an administrative bridge to the President University Information System (PUIS); and (3) the Academic Information System (PUIS) itself, providing real-time academic data. By leveraging gamification principles within a mobile-first approach, the system aims to make learning more interactive and rewarding. This paper presents the design and implementation of the gamification framework, with an ongoing evaluation to assess its impact on student engagement, motivation, and academic performance. Initial findings indicate that mobile gamification can effectively enhance participation, foster a sense of achievement, and create a more dynamic learning environment.